The Impact of Cervical Effacement at Time of Amniotomy in Patients Undergoing Induction of Labor - Rimsza, Rebecca R.; Kelly, Jeannie C.; Frolova, Antonina I.; Odibo, Anthony A.; Carter, Ebony B.; Cahill, Alison G.; Raghuraman, Nandini (American Journal of Perinatology, 2023)
Objective There is evidence to suggest that early amniotomy during induction of labor is advantageous. However, following cervical ripening balloon removal, the cervix remains less effaced and the utility of amniotomy in this setting is less clear. We investigated whether cervical effacement at the time of amniotomy impacts outcomes among nulliparas undergoing induction of labor.Study Design This was a secondary analysis of a prospective cohort of singleton, term, nulliparous patients at a tertiary care center undergoing induction of labor and amniotomy. The primary outcome was completion of the first stage of labor. Secondary outcomes were vaginal delivery and postpartum hemorrhage. Outcomes were compared between patients with cervical effacement ≤50% (low effacement) and >50% (high effacement) at time of amniotomy. Multivariable logistic regression was used calculate risk ratios (RR) to adjust for confounders including cervical dilation. Stratified analysis was performed in patients with cervical ripening balloon use. A post hoc sensitivity analysis was performed to further control for cervical dilation.Results Of 1,256 patients, 365 (29%) underwent amniotomy at low effacement. Amniotomy at low effacement was associated with reduced likelihood of completing the first stage (aRR: 0.87 [95% confidence interval, CI: 0.78–0.95]) and vaginal delivery (aRR: 0.87 [95% CI: 0.77–0.96]). Although amniotomy at low effacement was associated with lower likelihood of completing the first stage in all-comers, those who had amniotomy performed at low effacement following cervical ripening balloon expulsion were at the highest risk (aRR: 0.84 [95% CI: 0.69–0.98], p for interaction = 0.04) In the post hoc sensitivity analysis, including patients who underwent amniotomy at 3- or 4-cm dilation, low cervical effacement remained associated with a lower likelihood of completing the first stage of labor.Conclusion Low cervical effacement at time of amniotomy, particularly following cervical ripening balloon expulsion, is associated with a lower likelihood of successful induction.Key Points
Keywords: induction; amniotomy; nulliparous; cervical effacement